A Training on Designing 3D-Based on Instructional Media to Enhance Elementary Student Motivation - Zahroh, Mihnatuz; Arianto, Fajar; Maureen, Irena Y. (Abdi Cendekia : Jurnal Pengabdian Masyarakat, 2025)
Elementary school teachers often struggle with integrating 3D-based instructional media due to limited digital skills, hindering efforts to enhance student motivation through innovative learning tools. While 3D media like Assemblr EDU enhances student engagement, prior research has largely ignored the need for teacher training in utilizing such media effectively. This study evaluated the impact of a structured training program on teachers' competencies in developing 3D instructional media, with the ASSURE model serving as a guide for teachers to select and create appropriate media during the training. Employing a qualitative descriptive approach, data from 40 elementary teachers were gathered through observations, interviews, and feedback forms. Findings showed significant improvements in digital skills, with 75% completing 3D media projects and over 50% ready to implement them in classrooms. This training effectively bridged digital gaps and fostered pedagogical innovation, underscoring the importance of structured professional development for transforming learning practices and motivating students. Advanced training and continuous support are recommended for sustained technology integration.